MORFOLOGI VISUAL DALAM KESENIAN BADOGAR SANGGAR GENTRA SAWARGI KABUPATEN GARUT - Rahayu, Suci; Sujana, Anis; Ramli, Zaenudin (Jurusan Seni Rupa STSI Bandung, 2020)
Badogar is an acronym for Barong Domba Garut (Barong of Garut Sheep). It is a new art in Garut Regency resulted from creativities of its creators, namely Cecep Surachman and artists of Sanggar Gentra Sawargi. This study aims to describe the visual morphology in the art of Badogar that underwent changes in visual forms of the sheep’s head and the barong’s head. The approaches used in the study were aesthetic morphology and synchronous history. Results of the study focusing on visual morphology in Badogar art by Cecep Surachman and Sanggar Gentra Sawargi artists show two visual form structures of the Sheep’s head and the Barong’s head. Visual morphology in Badogar art is said to have gone through modification of forms in which its newly-created forms do not change the characterization of its original forms. Basically, the modification of these forms took place without any rules or standards so that changes and evelopment could be done according to the wishes of its creator and its artists.Keywords: Morphology, Visual, Badogar Art________________________________________________________________ Kesenian Badogar merupakan singkatan dari Barong Domba Garut. Kesenian Badogar merupakan kesenian baru di Kabupaten Garut yang merupakan hasil pemikiran kreator penciptanya yaitu Cecep Surachman dan seniman Sanggar Gentra Sawargi. Penelitian ini bertujuan untuk mendeskripsikan morfologi visual dalam kesenian Badogar yang mengalami perubahan bentuk visual pada Kepala Domba dan Kepala Barong. Pendekatan penelitian yang dilakukan adalah pendekatan morfologi estetik dan sejarah sinkronik. Hasil penelitian terhadap morfologi visual dalam kesenian Badogar karya Cecep Surachman dan seniman Sanggar Gentra Sawargi ini menunjukkan dua struktur bentuk visual Kepala Domba dan Kepala Barong. Morfologi visual dalam kesenian Badogar dikatakan mengalami modifikasi bentuk dimana bentuknya diciptakan terjadi tidak merubah perwatakan bentuk asal. Pada dasarnya modifikasi bentuk ini terjadi tanpa adanya pakem atau aturan, menjadikan perubahan dan untuk pengembangan dilakukan kebebasam sesuai keinginan pencipta dan senimannya sendiri.Kata Kunci: Morfologi, Visual, Kesenian Badogar